Does the COVID-19 crisis mark a turning point on the apprenticeship market? A forecast of the possible development of new apprenticeship contracts up until 2030 - Maier, Tobias [Verfasser] (My University, 2022)
“In 2020, in the wake of the COVID-19 crisis, the number of newly concluded apprenticeship contracts decreased by 57,600 compared to the previous year and reached the lowest level recorded since 1975. This article demonstrates that this collapse was only so severe because a surprisingly large amount of young people, particularly those in possession of a higher education entryqualification, had begun company-based training in the three years preceding. From a demographic perspective, the low level of training contracts was predictable. The question arising in future will be whether transition rates among young people stay at the low level of 2020 and what long-term implications this will produce in regard to securing the supply of skilled workers.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2 Übergänge; G 1.3.1.1 Ausbildungsstellenmarkt; 370; Berufsausbildung; Ausbildungsstellenmarkt; Pandemie; Einmündungsquote; Projektion; 2020-2030